Nigeria’s countertrade deal with Brazil under the Military: 1984-1985 (2017)
Nigeria after the attainment of independence in 1960 has been engaged in the global economic space. She was incorporated into the global capitalist System as a primary producer of agricultural produce. The quadrupling prices of crude oil in the international market in 1973 after its discovery in Nigeria in 1958 further positioned the country strategically in global oil market. However, the global economic meltdown which brought the crude oil prices in the international market to all time low in the 1980s made the concept of Countertrade a key strategy of survival for countries whose prices of resource endowments were affected by the global economic meltdown. Nigeria and Brazil engaged in this trade as they exchanged crude oil, consumable goods and industrial equipment. Against this backdrop, this paper examines the Countertrade with Brazil and argues that, the possession of resources is not enough to ensure survival, but Strategic deployment of such endowments determines the extent to which the unconventional strategy of a nation like Nigeria can enable it explore the volatile international economy.